Inoculation effect of Azospirillum sp. and two levels of nitrogen on the performance of the hybrid corn ‘Insignia 800' - Contreras-Liza, Sergio Eduardo (2020)
The objective of this investigation was to evaluate the effect of inoculating Azospirillum sp. and two levels of nitrogen on the productive characteristics of hard yellow corn variety  ‘Insignia 800’ under the conditions of Nuevo Imperial, Cañete (central coast of Peru). A randomized complete block design with five treatments and four replications was used in a field experiment using the commercial corn hybrid ‘Insignia 800’. The treatments were two levels of nitrogen (90 and 180 kg N ha-1), plus one or two applications to the foliage of Azospirillum sp. (1.08 x 107 CFU per plant), and a control treatment (without inoculation). Ten agronomic variables related to productive traits were evaluated. Treatment comparison was executed with the Scott Knott test at the 5% significance level using the Infostat program. Inoculation with Azospirillum sp. did not significantly affect the grain yield per hectare, grain weight per plot, shelling percentage, grain depth, number of ears per plant and diameter of the cob, but it influenced significantly some productive traits such as cob weight per plot, grain weight per plant, cob diameter and ear length, as well as a high benefit-cost ratio due to inoculation. Inoculating the plant foliage with Azospirillum sp. had a significant effect and greater economic efficiency for some productive characteristics of the hard yellow corn cv. ´Insignia 800´, and did not significantly affect grain yield.